Potential Impact of Body Mass Index on the Clinical Outcome of Papillary Thyroid Cancer After High-Dose Radioactive Iodine Therapy - Cao, Jingjia; Zhu, Xiaolu; Sun, Yaru; Li, Xiao; Yun, Canhua; Zhang, Wei (Frontiers in Endocrinology, 2022)
Context: Obesity has been reported as a potential risk factor for aggressiveness of papillary thyroid cancer (PTC), but the data gathered so far are conflicting. Objective: The aim of our study was to evaluate the relationship between body mass index (BMI), aggressiveness of PTC at the diagnosis and clinical outcome. Methods: A total of 337 patients who underwent RAI therapy from March 2017 and May 2020 were recruited. Patients were divided into four groups: underweight (BMI<18.5 kg/m2), normal weight (18.5-24.9 kg/m2), overweight (25-29.9 kg/m2) and obese (BMI≥ 30 kg/m2). Treatment and follow-up were defined according to criteria used in the 2015 ATA guidelines. Results: This study included 337 patients with PTC (71.5% females, median age 45.21±13.04 years). The mean BMI was 24.2 ± 3.1 kg/m2. Obese groups have a higher age than the other groups (P = 0.001). Moreover, obese patients had more tumor size and higher T stage, compared to overweight, normal weight and underweight patients (P = 0.007). After a median follow-up of 32 months, 279 patients (82.7%) had achieved excellent response to therapy. The overall ER reached rates was compared between groups, and there was not differ significantly. Conclusions: we demonstrated that the BMI may have additive effect on the aggressiveness, but have not effect on response to therapy after high-dose radioactive iodine therapy.